Leopold III and the Belgian Royal Question - Arango, E. Ramón (Johns Hopkins University Press, 1963)
Originally published in 1963. Between 1945 and 1951, Belgium faced a crisis in political leadership when its ruling monarch, King Leopold III, was accused of violating the Belgian Constitution during World War II. The "question" at hand refers to the uncertainty over whether King Leopold III could return to Belgium as king. This book documents the history of this political crisis, culminating with the abdication of King Leopold and the assumption of the crown by Baudouin, Leopold's son.